2016
DOI: 10.1590/s0100-83582016340200010
|View full text |Cite
|
Sign up to set email alerts
|

Weed Interference Periods in Early Wheat in the Midwest of Paraná

Abstract: -Several factors can influence wheat crop yield, they include the interference imposed by weeds is one of the most important. The objective of this study was to evaluate the critical periods of weed interference in early wheat in the midwest of the state of Paraná, Brazil. The experiment was conducted in an experimental area located in Campo Mourão -PR, during the year 2013, using the BRS Pardela cultivar. The treatments consisted of periods of coexistence and weed control in wheat. Periods of coexistence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The critical period for preventing weed interference in wheat is at the beginning of its growing cycle. At this stage, weeds enhance their biomass due to favorable environmental conditions (Silva et al, 2016). If weeds such as Canada thistle are controlled at the early growth stages, the effectiveness of the chemical treatment may be improved.…”
Section: Resultsmentioning
confidence: 99%
“…The critical period for preventing weed interference in wheat is at the beginning of its growing cycle. At this stage, weeds enhance their biomass due to favorable environmental conditions (Silva et al, 2016). If weeds such as Canada thistle are controlled at the early growth stages, the effectiveness of the chemical treatment may be improved.…”
Section: Resultsmentioning
confidence: 99%
“…PBI was estimated considering a 5% reduction in crop maximum productivity in each of the management, being defined as the average cost to control the weed community present (Silva et al, 2015;Silva et al, 2016;Agostinetto et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…However, the critical period of weedcompetition was determined to be between 30 and 50 days after sowing of wheat. In a more recent study, Silva et al [34] found that the number of reproductive tillers per plant and spikelets per spike, spike length, plant height and wheat crop yield were significantly affected by coexistence with prevailing infestation of wild radish (Raphanus raphanistrum L.), and the critical period of interference was determined at 16 to 24 days after crop emergence.…”
Section: Introductionmentioning
confidence: 99%